Reservoir classification and evaluation of Yan'an formation in Xifeng Oilfield. Issue 1 (June 2020) - Sun, Ning; Zhang, Zhipeng; Li, Zhenhua; Chen, Zhanjun
Abstract: According to reservoir lithology and the combination of pore throat, this paper takes porosity, permeability, pore throat diameter and displacement pressure as evaluation parameters to classify and evaluate the reservoir. Yan'an Formation reservoir in Xifeng Oilfield is divided into four types, I, II, III and IV, which correspond to four types of good, medium, poor and non reservoir respectively.From class I to class IV reservoir, the reservoir performance changes from good to bad, the porosity and permeability decrease, and the heterogeneity increases. The results of geological analysis show that the classification results are reasonable and have certain guiding significance for the exploration and development of oil and gas in the oilfield.